Criteria for obtaining the grant of a patent of invention in Peru - Arana Courrejolles, María del Carmen (2015)
This article is a casuistry review of technical reports of several filesregarding applications of patent of invention, in the technological fields of biotechnology, pharmaceutics, chemistry and engineering, where in general and specific criteria are identified and extracted on the requirements of clearness and inventive step that are evaluated in the technical report for obtaining a patent of invention in Peru.It is important to note that prior to the review of the investigated technical reports, certain definitions are provided for understanding the requirements of the technical report, such as conciseness, clearness, sufficiency, novelty and inventive step.